Comparative Genome Analyses of Clavibacter michiganensis Type Strain LMG7333T Reveal Distinct Gene Contents in Plasmids From Other Clavibacter Species - Oh, Eom-Ji; Hwang, In Sun; Park, In Woong; Oh, Chang-Sik (Frontiers in Microbiology, 2022)
Clavibacter michiganensis, a Gram-positive, plant-pathogenic bacterium belonging to Actinobacteria, is a causal agent of bacterial canker in tomatoes. Although LMG7333T is the type strain of C. michiganensis, it has not been used in many studies, probably because of a lack of the complete genome sequence being available. Therefore, in this study, the complete genome sequence of this type strain was obtained, and comparative genome analysis was conducted with the genome sequences of two other C. michiganensis strains and type strains of Clavibacter species, of which their complete genome sequences are available. C. michiganensis LMG7333T carries one chromosome and two plasmids, pCM1 and pCM2, like two other C. michiganensis strains. All three chromosomal DNA sequences were almost identical. However, the DNA sequences of two plasmids of LMG7333T are similar to those of UF1, but different from those of NCPPB382, indicating that both plasmids carry distinct gene content among C. michiganensis strains. Moreover, 216 protein-coding sequences (CDSs) were only present in the LMG7333T genome compared with type strains of other Clavibacter species. Among these 216 CDSs, approximately 83% were in the chromosome, whereas others were in both plasmids (more than 6% in pCM1 and 11% in pCM2). However, the ratio of unique CDSs of the total CDSs in both plasmids were approximately 38% in pCM1 and 30% in pCM2, indicating that the high gene content percentage in both plasmids of C. michiganensis are different from those of other Clavibacter species, and plasmid DNAs might be derived from different origins. A virulence assay with C. michiganensis LMG7333T using three different inoculation methods, root-dipping, leaf-clipping, and stem injection, resulted in typical disease symptoms, including wilting and canker in tomato. Altogether, our results indicate that two plasmids of C. michiganensis carry distinct gene content, and the genome information of the type strain LMG7333T will help to understand the genetic diversity of the two plasmids of Clavibacter species, including C. michiganensis.